Inventory management study on Furniture Source Philippines - Bontia, Roberto Mari M.; Kabigting, Matthew Edmund T.; Ongson, Erick Spencer T.; Ramos, Edric Delwyn L.
Furniture Source Philippines is a small business enterprise in the furniture industry. Its current inventory management system relies solely on human judgment when ordering stocks from suppliers abroad. As a result, the overstocking of class A items is prominent, which consequently incurred P3,978,839.05 in total holding cost for 2015. This study aims to compute for target inventory levels using the Fixed Order Interval (FOI) inventory management system to minimize total holding cost. Through the computing of target inventory levels, the total holding cost decreased by 42.42%. By reducing the holding cost, the company's warehouse storage will no longer extend to their showroom. Their storeroom will look less cluttered and could encourage more sales.